Pneumatosis Coli Treated with Metronidazole and Hyperbaric Oxygen Therapy: A Successful Case - Costa, Mariana (2015)
Pneumatosis intestinalis, characterized by the presence of gas within the bowel wall, is an uncommon condition with variablepresentation. It may be idiopathic or secondary to other diseases. A computed tomography scan is the most sensitive method for diagnosis. In the absence of signs and symptoms of complications, such as perforation and peritonitis, pneumatosis intestinalis can bemanaged conservatively. We present the case of a 59-year-old woman with pneumatosis coli secondary to benign ovary teratoma. After surgery she remained symptomatic and was successfully treated with metronidazole and hyperbaric oxygen therapy.